Assessing effects of temperature driven by sowing dates on the grain filling and kernel weight of corn in the North China Plain - An, Panpan; Liu, Kui; Zhang, Moubiao; Zhou, Shunli; Jia, Xucun; Wang, Xiuling; Dong, Pengfei; Zhao, Yali; Wang, Qun; Li, Chaohai; Liu, Tianxue (Frontiers in Plant Science, 2025)
IntroductionThe grain filling process is strongly influenced by weather during the reproductive growth stage, but grain filling and yield of corn under various weather conditions resulting from different sowing dates remain uncertain.MethodsA two-year study was conducted at Henan Agricultural Research Farm in 2015 and 2016 to investigate the grain filling dynamics of corn under different temperatures that were modified through four distinct sowing dates: spring sowing in late April, early summer sowing in late May, summer sowing in mid-June, and autumn sowing in early July.ResultsThe findings indicated that the elevated temperatures in 2016 led to an 8.7% reduction in yield and a 7.4% decrease in 1000-kernel weight compared to the normal temperatures in 2015, attributed to a shortened grain filling period resulting from the higher temperature (31.6°C). Significant differences in yield were observed across the four sowing dates. Findings from this study also highlighted that growing degree-days had a weak direct, but a strong indirect positive effect on thousand kernel weight through the grain filling duration. The average daily temperature had a weak direct negative, but a strong indirect positive effect on kernel weight through mean grain filling rate.DiscussionWith the global climate changing, the intensity and frequency of high temperatures are expected to increase. To reduce corn yield loss due to high temperature in North China Plain advancing sowing dates from mid-June to late May is recommended. It is concluded that early sowing could effectively prolong the active grain filling duration and offset the decline in grain filling rate caused by high temperatures. The findings demonstrated advancing sowing dates improved the grain filling and yield of summer corn, thereby mitigating high temperature stress under global warming.